1991
DOI: 10.4050/jahs.36.61
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Automated Nap‐of‐the‐Earth Rotorcraft Flight

Abstract: In this paper, we consider nap-of-the-earth WOE) rotorcraft flight as one of the applications in which ohstncle avoidance plays a key role, and investigate the prospects of automating the guidsnrc functions of NOE flight. Based on a proposed structure far the guidance functions, we identify obstsclc detection and ohstnclc avoidance as the two critical components requiring substantial advancement before an automatic guidance system can he realized. We discus the major sources of difficulties in developing these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…O<u, <1; i=1,2,...,K, j=1,2,...,N (1) j=1,2,...,N (2) O<u1<N; i=1,2,...,K This fuzzy K-partition can be defined as a fuzzy segmentation. Furthermore, if we define a uniformity predicate P(u13) such that it assigns the value true or false to the sample point x based on its membership value, we will have paralleled the crisp segmentation.…”
Section: Iterative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…O<u, <1; i=1,2,...,K, j=1,2,...,N (1) j=1,2,...,N (2) O<u1<N; i=1,2,...,K This fuzzy K-partition can be defined as a fuzzy segmentation. Furthermore, if we define a uniformity predicate P(u13) such that it assigns the value true or false to the sample point x based on its membership value, we will have paralleled the crisp segmentation.…”
Section: Iterative Methodsmentioning
confidence: 99%
“…Automated rotorcraft low-altitude flight using passive range estimation algorithms is described in the literature [1,2,3]. Some range estimation algorithms produce range information corresponding to small discrete sparse areas (features) in the image.…”
Section: Introductionmentioning
confidence: 99%
“…The reference state and control vectors, x 0 and u 0 , are provided by the inverse solution of the equations of motion. A design condition of rectilinear level flight at 30ms- 1 , where the unaugmented system is slightly unstable, is chosen for the present study, which corresponds to the velocity value indicated in Ref. 1 for a typical NOE flight.…”
Section: ^=F((y-yo) R Q(y-yo)+(«-«o) R R(«-u"))^ •••05)mentioning
confidence: 99%
“…4 The prediction can be integrated in a ground proximity warning system, to reveal a possible ground collision with a time margin sufficient for undertaking an appropriate control action for avoiding obstacles on the prescribed flight path. In this case, the knowledge of an envelope of feasible future positions is also useful, if an efficient guidance law for obstacle avoidance is sought.…”
mentioning
confidence: 99%